The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1109/access.2021.3059343
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Prediction of Diabetes Using Data Mining: A Comprehensive Review

Abstract: Diabetes is one of the most rapidly growing chronic diseases, which has affected millions of people around the globe. Its diagnosis, prediction, proper cure, and management are crucial. Data mining based forecasting techniques for data analysis of diabetes can help in the early detection and prediction of the disease and the related critical events such as hypo/hyperglycemia. Numerous techniques have been developed in this domain for diabetes detection, prediction, and classification. In this paper, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 111 publications
0
11
0
1
Order By: Relevance
“…GA is used to reduce insignificant features in this study. We defined chromosomes as a mask for characteristics to achieve this goal [ 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…GA is used to reduce insignificant features in this study. We defined chromosomes as a mask for characteristics to achieve this goal [ 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes, a global problem, has become one of the three biggest threats to human health. Patients with diabetes who do not receive adequate treatment will develop cardiopulmonary diseases, liver complications, nerve damage, etc., which can seriously affect their health ( 9 ). In this situation, early diagnosis and prevention of diabetes are critical.…”
Section: Related Work In the Field Of Big Datamentioning
confidence: 99%
“…The predictive values of this study lie on the unit interval i.e., in between 0 and 1. Khan et al [2] presented the various data mining techniques for diabetes detection, classification and prediction. In this study it is concluded that for accurate results the data should be pre-processed and parallel models should be used instead of one.…”
Section: Related Workmentioning
confidence: 99%